Texica Limited (C) : learning from the exit interviews - Maheshwari, Sunil Kumar; Ray, Prantika (London : Indian Institute of Management, Ahmedabad, 2017)
Texica Limited, a renowned textile company had been reporting losses for the past few years. The Chairman, Ashutosh Verma decided to seek help from Dr. Asim Vakil and his team of consultants to improve the performance of the company. One of the most important problems in the organization was the loss of talent through attrition. Vikal conducted exit interviews with two Texica employees leaving the company for a rival firm in order to understand why the Texica had an attrition rate of 15% to 20%.
Originally Published InMaheshwari, S. K., & Ray, P. (2017). Texica Limited (C): Learning from the exit interviews. HRM0239(C). Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Labor turnover -- Case studies; Performance standards -- Case studies; Exit interviewing -- Case studies; Personnel management -- Case studies